Implementasi Kurikulum 2013 Mata Pelajaran Bahasa Indonesia pada Teks Surat Pribadi dan Surat Dinas di Kelas VII SMP Negeri Lubuk Tua Kabupaten Musi Rawas - Lisanti, Farida; Yulistio, Didi; Basuki, Rokhmat (UNIB Press, 2021)
The purpose of this study was to describe the implementation of the 2013 curriculum for Indonesian subjects in the text of personal letters and official letters in class VII SMP Negeri Lubuk Tua, Musi Rawas Regency, especially in preparing learning implementation plans or RPP, implementation of learning, authentic assessment. The method used is descriptive method. The source of the data for this research is the Indonesian language teacher who teaches students in grade VII SMP Negeri Lubuk Tua. The data in this study were in the form of RPP document data, words, behavior, and learning implementation activities in learning the text of personal letters and official letters. Data collection techniques were carried out by interviewing, observing, and documenting. The data analysis technique was carried out in the following steps: 1) data reduction, namely by grouping the data in interviews, documentation, and observations; 2) data presentation is done by classifying and outlining the data of the Learning Implementation Plan, implementation of learning, authentic assessment; (3) data interpretation, evaluation and analysis are carried out according to the problem to draw conclusions. The results showed that teachers had understood the 2013 Curriculum with evidence that they had prepared the lesson plans well, had prepared personal texts and official letters according to the basic competencies achieved, carried out learning activities according to the lesson plans, and and in authentic assessment activities the teacher still focuses on applying attitude and knowledge assessment.